Samyeketik Hindi-Sanyunkta rastra bhasha-kosh - Central Hindi directorate (New Delhi Central Hindi directorate, 2002)
Consolidated Hindi- U.N. languages dictionary(Hindi-English, Arabic, Chinese, French, Russian, Spanish )
Keywords: (Hindi-English, Arabic, Chinese, French, Russian, Spanish )